Verbos : Palabras que Describen Acciones - 20160731 frey50 (Danbury, CT Grolier/Hatchette, 1994)
Verbs, bilingual text.
Illustrated with Disney characters.
Keywords: Andrade, Jose Lopez; Couto, Tomas Rodriguez; Walt Disney Company - Juvenile literature; Spanish - English - Bilingual - Juvenile literature